Romanticism - Gunderson, Jessica (Mankato, Minn. : Creative Education, 2009)
Examines the birth and decline of the romantic movement in art which stretched from the mid-eighteenth century to around 1850, looks at the political and social events that sparked romanticism, and introduces representative artists and works.
Includes bibliographical references (p. 47) and index.
8.4
5-8
Keywords: Romanticism in art -- Juvenile literature; Romanticism in art; Romanticism in art